2017
DOI: 10.1177/0091217417720893
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between coping, emotion regulation, and quality of life of patients on dialysis

Abstract: Previous studies have investigated constructs that facilitate adaptation to chronic disease and improve quality of life and constructs that lead to psychopathological complications. The purpose of this research is to investigate the impact of coping and emotional regulation on the quality of life of patients on dialysis. Three questionnaires were administered to 78 patients on dialysis: Coping Orientations to Problems Experienced, Short Form (36), and Cognitive Emotion Regulation Questionnaire. Regressions ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 27 publications
1
22
1
1
Order By: Relevance
“…Participants particularly found comfort in the communication styles of the providers and welcomed the support given to cope with their disease. In CKD, a disease with multiple stressors, coping mechanism are associated with quality of life, 30 therefore improving one's ability to cope with disease can have significant impact. In Urquart-Secord et al's study which aimed to identify outcomes of importance to hemodialysis patients and their caregivers, capacity to cope was identified as a key subtheme in their qualitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Participants particularly found comfort in the communication styles of the providers and welcomed the support given to cope with their disease. In CKD, a disease with multiple stressors, coping mechanism are associated with quality of life, 30 therefore improving one's ability to cope with disease can have significant impact. In Urquart-Secord et al's study which aimed to identify outcomes of importance to hemodialysis patients and their caregivers, capacity to cope was identified as a key subtheme in their qualitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…5 Penelitian yang dilakukan Barberis dan kawan-kawan menegaskan bahwa strategi koping yang berfokus pada masalah akan memberikan kualitas hidup yang lebih baik, sedangkan strategi koping yang berpusat pada emosi akan memberikan dampak yang kurang baik pada kualitas hidup. 6 Kualitas hidup adalah persepsi individu tentang posisi mereka dalam kehidupan dalam konteks budaya dalam sistem nilai dimana mereka tinggal dan dalam hubungan mereka dengan tujuan, harapan, standar hidup dan masalah. Beberapa hal yang dapat memengaruhi kualitas hidup diantaranya sosio-ekonomi-kultural setempat, kondisi kesehatan fisik/psikis (mental emosional).…”
Section: Pendahuluanunclassified
“…In terms of the effectiveness of the acceptance component in controlling diabetes' indices, it can be claimed that increasing acceptance in people with diabetes makes them more concerned about themselves and their health, so they try to take their medicines and insulin on time, better follow the diet recommended, do more physical activities, and measure blood sugar daily, which together improve the body's metabolism and positively affect blood sugar, self-care behaviors, and finally quality of life (38,39). As a result, it can be stated that the findings of this study are consistent with the studies of Hadlandsmyth et al (40) and Gregg et al (41), who showed the effectiveness of acceptance and commitment therapies on the self-care of patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%